O impacto da terceirização do call center em empresas de energia elétrica no Brasil - Torres, Raphael Fernandes (2006)
This dissertation seeks to recognize the impacts that outsourcing of the call center brings to firms of electrical energy in Brazil. For this research, two existing cases in the brazilian sector electric: i) case of Cemig, firm mineira of electrical energy; ii) case Light, firm carioca of electrical energy. The framework of this dissertation is based of the methodology of multiple study cases described by Robert Yin (2003). This work analyzed separately each of the cases and compared the results obtained in each analysis. In this way, this research aimed at analyzing the impacts that firms sufering in outsource the call center, despite the citys are diferents, like the factors of the environment. The obtained results suggest that the firms adopt the mixed call center, with the greatest part of outsources employees and with less proper. The importants impacts seeks in this research are the lost of the image, quality and the control of the process of answering. The aim impacts of a outsourcing the call center find in this research are the lost of the image of the firm and the reduction of the control of the process of customer service, impacting directly on the quality of the customer service.